Study on rock damage mechanics in the sustainable development of the red sandstone area in China: Taking Zhongjiang County as an example - Li, Ailin; Zhong, Wenwu; Yu, Cong; Zhang, Xin; Li, Tao; Fei, Zheng (Frontiers in Earth Science, 2025)
There are many hilly areas dominated by red sandstone in western China. At the same time, China is also rapidly advancing the modernization of sustainable development in the abovementioned areas. Therefore, in order to ensure the safety and sustainable advancement of modernization, it has become an urgent task for the local government to explore the mechanical properties of red sandstone in relevant areas. Zhongjiang County, Sichuan Province, China, is mainly dominated by red sandstone, and the study of red sandstone in this area is very rare. Therefore, this paper takes the red sandstone in Zhongjiang County as the research object and studies the damage evolution characteristics of red sandstone under the uniaxial compression load using the acoustic emission monitoring technology. The results show that when the axial stress of red sandstone shows a V-shaped evolution phenomenon and the acoustic emission ringing count enters a relatively quiet period, it indicates that the red sandstone will undergo instability failure. By exploring the evolution law of Ф (AF (ringing count/duration)/RA (rise time/amplitude)), the evolution characteristics of fracture types of red sandstone in the process of damage were found. Based on Weibull function and continuum damage mechanics, the damage evolution model and stress–strain constitutive model are derived. Based on the evolution law of damage variables, the damage evolution characteristics of red sandstone are quantitatively characterized. The research findings provide the government of Zhongjiang County with a reference basis for formulating sustainable construction plans.